PELATIHAN ANAK YATIM DAN DHUAFA DALAM UPAYA MENINGKATKAN PENGGUNAAN MICROSOFT WORD DAN MICROSOFT EXCEL DI ASRAMA DOMYADHU CABANG CIPUTAT - dona katarina; Ida Fitriani (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
Along with the development of Information Technology, computers and their use in everyday life are used to process data into information. One of the important programs that a computer user must have and control is Microsoft Office. As the name implies, this program can help to do data processing work more easily. In Microsoft Office there are many types of programs that can be used, for example Microsoft Word and Microsoft Excel. Microsoft Word is a program that is very important in everyday life. This program is a word processing program that includes creating, editing and formatting documents. Meanwhile, Microsoft Excel is a program designed to perform number processing. The Unindra community service team will carry out community service activities at the Domyadhu Foundation in the Ciputat branch by providing training on the use of Microsoft Word and Microsoft Excel. By conducting this training, it is hoped that it can improve knowledge on the use of Microsofot Word and Microsoft Excel for younger siblings at the Foundation.